dLp/HDL-BGBP and MTP Cloning and Expression Profiles During Embryonic Development in the Mud Crab Scylla paramamosain - Zeng, Xianyuan; Lyu, Liang; Zhao, Dousha; Zhong, Jinying; Feng, Yan; Wan, Haifu; Li, Chunyang; Zhang, Ziping; Wang, Yilei (Frontiers in Physiology, 2021)
Lipids are the main energy source for embryonic development in oviparous animals. Prior to utilization and catabolism, lipids are primarily transported from the yolk sac to embryonic tissues. In the present study, cDNA encoding a circulatory large lipid transfer protein (LLTP) superfamily member, the precursor of large discoidal lipoprotein (dLp) and high density lipoprotein/β-1,3-glucan-binding protein (HDL-BGBP), named dLp/HDL-BGBP of 14,787 bp in length, was cloned from the mud crab Scylla paramamosain. dLp/HDL-BGBP was predicted to encode a 4831 aa protein that was precursor of dLp and HDL-BGBP,, which were both detected in hemolymph by LC-MS/MS analysis. For the intracellular LLTP, three microsomal triglyceride transfer protein (MTP) cDNAs of 2905 bp, 2897 bp, and 3088 bp in length were cloned from the mud crab and were predicted to encode MTP-A of 881 aa, MTP-B of 889 aa, and MTP-C of 919 aa, respectively, which were different merely in the N-terminal region and shared an identical sequence of 866 aa. During embryonic development, the expression level of dLp/HDL-BGBP consecutively increased from the early appendage formation stage to the eye pigment-formation stage, which indicated that HDL-BGBP is probably the scaffolding protein for yolk lipid. For the MTP gene, MTP-C accounted for approximately 70% of MTP mRNA from the blastocyst stage to the nauplius stage, as well as the pre-hatching stage; MTP-C and MTP-A expression levels were comparable from the early appendage formation stage to the late eye pigment-formation stage; MTP-A was extremely low in blastocyst and gastrula stages; MTP-B was expressed at a relatively low level throughout embryo development. The variations in expression profiles among MTP transcripts suggested that MTP might play roles in lipid droplet maturation and lipoprotein assembly during embryonic development.